2015
DOI: 10.1124/jpet.115.226431
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Deficiency Diminishes Indomethacin-Induced Intestinal Epithelial Cell Damage through Activation of the ERK/Nrf2/HO-1 Pathway

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) can cause epithelial cell damage in the stomach, intestine, and colon. NSAIDs are reported to induce autophagy and apoptosis in intestinal epithelial cells; however, their role in cell damage is poorly understood. To examine the role of autophagy in cell damage, we used autophagy-related gene Atg5-conditional knockout mice, in which the Atg5 gene is only knocked out in intestinal epithelial cells. In an indomethacin (IM)-induced gastrointestinal ulcer mouse model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
(38 reference statements)
2
32
0
Order By: Relevance
“…In this study, both INDO and DIC were able to induce cytotoxicity in human intestinal Caco‐2 cells possibly via production of ROS, ER stress and mitochondria dysfunction. Several studies suggested that ROS was an underlying cause of intestinal cell damage after exposure to either INDO or DIC . Both INDO and DIC were able to increase intracellular ROS in intestinal Caco‐2 cells possibly through inhibiting mitochondrial complex I activity .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, both INDO and DIC were able to induce cytotoxicity in human intestinal Caco‐2 cells possibly via production of ROS, ER stress and mitochondria dysfunction. Several studies suggested that ROS was an underlying cause of intestinal cell damage after exposure to either INDO or DIC . Both INDO and DIC were able to increase intracellular ROS in intestinal Caco‐2 cells possibly through inhibiting mitochondrial complex I activity .…”
Section: Discussionmentioning
confidence: 99%
“…In GES-1cells, HO-1 was increased about 2.16 folds compared with that of control group and NQO1 was increased about 1.66 folds. In SGC-7901 cells, HO-1 was increased [4,20] .…”
Section: Resultsmentioning
confidence: 91%
“…ER stress and apoptosis are involved in NSAID-induced ulcers in stomach and intestine (Tsutsumi et al, 2004;LoGuidice et al, 2010;Ohyama et al, 2012;Harada et al, 2015). TPPU might have decreased the number of ulcers by suppressing ER stress, because sEH inhibition and sEH gene deletion are reported to decrease ER stress in different disease models (Bettaieb et al, 2013;Harris et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…TPPU might have decreased the number of ulcers by suppressing ER stress, because sEH inhibition and sEH gene deletion are reported to decrease ER stress in different disease models (Bettaieb et al, 2013;Harris et al, 2015). NSAIDinduced intestinal ulcers are characterized by apoptosis of intestinal epithelial cells (Harada et al, 2015). EETs, sEH inhibition, and sEH gene deletion decrease apoptosis of cells (Luo et al, 2010;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%